A Comment on Newman's "Complete Ordering and Revealed Preference" - Uzawa, Hirofumi (Review of Economic Studies, 1961)
A Comment on Newman's “Complete Ordering and Revealed Preference” Get access Hirofumi Uzawa Hirofumi Uzawa Berkeley, California Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 28, Issue 2, February 1961, Pages 140–141, https://doi.org/10.2307/2295712 Published: 01 February 1961